Agronomic and organizational aspects of Barcelona’s community gardens - Macall, Diego Maximiliano; Durany, Xavier Gabarrell; Villamayor-Tomas, Sergio (Frontiers in Sustainable Food Systems, 2025)
As food security becomes a growing concern in urban areas worldwide, municipal authorities are actively seeking ways to enhance and complement the food systems of their respective cities. Integrating a food system’s productive components within city limits has emerged as a promising strategy to achieve these goals. However, it is impractical to undertake urban agriculture to the extent of rural agriculture, such as livestock rearing and large-scale field crop production, due to insufficient and inadequate space within cities. Producing high-value crops, however, is feasible and already practiced in many urban areas around the world within community gardens. This study investigates the agronomic practices and organizational aspects of community gardens within Barcelona’s municipal boundaries. It does so through surveys of community garden members and visual inspections of the gardens. The results show that 10 of the 22 most consumed vegetables in Barcelona are harvested within the city’s community gardens, highlighting their agrobiodiversity. Based on observed crop yields, if monoculture for each crop produced in the community gardens were practiced across all available urban areas in Barcelona, the city could achieve significant self-sufficiency in those crops. However, to realize this potential, urban horticulture would need to be professionalized, and the city’s municipal authorities would have to play a coordinating role.